2010
DOI: 10.1093/glycob/cwq046
|View full text |Cite
|
Sign up to set email alerts
|

NMR characterization and molecular modeling of fucoidan showing the importance of oligosaccharide branching in its anticomplementary activity

Abstract: Fucoidan is a potent inhibitor of the human complement system whose activity is mediated through interactions with certain proteins belonging to the classical pathway, particularly the protein C4. Branched fucoidan oligosaccharides displayed a higher anticomplementary activity as compared to linear structures. Nuclear magnetic resonance (NMR) characterization of the branched oligosaccharides and saturation transfer difference-NMR experiment of the interaction with the protein C4 allowed the identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…The original observations showed that fucoidan fractions from A. nodosum potently inhibit both the classical and alternative pathways in human serum [158]. Tissot and colleagues have extensively studied this activity [159,160,161,162]. It was determined that low molecular weight fucoidan fractions bind to the C1q subunit of the C1 complex that triggers complement through recognition and binding of immune complexes [162].…”
Section: Bioactivity and Structure-activity Relationshipmentioning
confidence: 99%
“…The original observations showed that fucoidan fractions from A. nodosum potently inhibit both the classical and alternative pathways in human serum [158]. Tissot and colleagues have extensively studied this activity [159,160,161,162]. It was determined that low molecular weight fucoidan fractions bind to the C1q subunit of the C1 complex that triggers complement through recognition and binding of immune complexes [162].…”
Section: Bioactivity and Structure-activity Relationshipmentioning
confidence: 99%
“…Crystallographic studies have identified a heparin binding site on the globular region of C1q (Garlatti et al, 2010). In addition, fucoidan also exerts anticomplement activity through interacting with C4; structural studies of the interaction between C4 and a fucoidan oligosaccharide have shown that branching enhances affinity (Clément et al, 2010).…”
Section: Heparin the Complement System And Innate Immunitymentioning
confidence: 99%
“…Fucoidans are known to be highly branched polysaccharides but the potential meaning of the branching structures in terms of bioactivity was not considered until Clement’s research of 2010 [60]. In an elegant NMR study, Clement tackles the structural heterogeneity and the random sulfation of the polysaccharide chain with relation to how they affect complement binding and inhibition.…”
Section: Inflammation and Fibrosismentioning
confidence: 99%